MATEMATIKA DALAM TOROI LADO DAHHA PADA UPACARA ADAT DI SUMBA BARAT NUSA TENGGARA TIMUR - Welhem Mine Wadu; Restisary Nduka; Timotius Woda Napu; Yohana Anggreni Talo; Apliana Toro Baju (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2026)
Abstract This study aims to examine mathematical concepts embedded in the practice of Toroi Lado Dahha in Lamboya indigenous community, West Sumba. The study is motivated by the importance of exploring mathematics embedded in local culture as part of ethnomathematics. This research employed a qualitative ethnographic approach through in-depth interviews with traditional leaders (Rato). The results show that Toroi Lado Dahha contains mathematical concepts such as basic arithmetic, number sequences, discrete time functions, and lunar calendar systems. The determination of ritual time is conducted through forward counting from the full moon phase and by observing the emergence of nyale, a type of sea worm that serves as the main indicator for Pasola timing. Furthermore, the system is not fixed but adaptive to natural conditions and cultural decisions. This study reveals that mathematics in Lamboya society is implicit and integrated with language, culture, and daily practices. These findings are important for developing contextual mathematics learning based on local culture. Keywords: Ethnomathematics, Toroi Lado Dahha, Counting System, Auspicious Days, Sumba Culture